Prevention of cross-infection due to the transmission of Covid-19 in orthodontic treatment during the pandemic: Pencegahan infeksi silang penyebaran Covid-19 dalam perawatan ortodonti pada masa pandemi - Ardiansyah S. Pawinru; As'ad Saefullah Gani (Makassar Dental Journal PDGI Makassar, 2021)
Background: In 2020, WHO declared the name of the Coronavirus disease 2019 (Covid-19). In the middle of the pandemic, orthodontists have limited their treatment. The challenges of the orthodontic profession in performing treatment become more difficult due to many factors, such as high saliva concentrations. Objective: To find out how to prevent cross-infection of Covid-19 in performing orthodontic treatment during the pandemic. Methods: By using a literature review, information that is relevant to the topic of the study is collected and then synthesized in an article. Results: It was found that there were similarities in the dis-cussion regarding the difficulty of consulting and taking active and inactive orthodontic treatment actions during the Covid-19 pandemic. Conclusion: In orthodontic treatment during this pandemic, dentists and clinical health staff must triage patients be-fore visiting the clinic and must carry out infection control management at the clinic, both orthodontic treatment procedures and other pressure.